ANALISIS EFISIENSI BIAYA OPERASIONAL PENGELOLAAN TAMAN WISATA TANJUNG BIRA TERHADAP PENDAPATAN DINAS PARAWISATA DAERAH KABUPATEN BULUKUMBA - Nurfaidah Nurfaidah (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2017)
The purpose of this study was to measure the extent of operational cost efficiency of the management of Parks Tourism promontory Bira and the effect on revenue Bulukumba District Tourism Department To know the development of promontory Bira Travel Park management Bulukumba district where the techniques of data collection that is used is to conduct a field study whether conducted through observation, interviews and documentation and study of literature to support the problems studied by the authors The analytical method used is the analysis of variance which in this study the authors compare the budget and realization both for operating costs and revenue district tourism office Bulukumba From the research conducted by the author that the difference harm caused differences in operational fuel costs Rp.1.723.295,- or 31.27% Difference in cost Security Rp.16.449.875,- or 802% Difference revenues adverse levies throughout Actual income items due to the income Levy Use parking area properties promontory Bira Points lodging Guest Houses Villa Funeral Dato Tiro, Bath hila – hila Pua cowboy , Lolisang , samboang beach and Bath Betu , dampang smaller than the specified budget. Tourism agency Bulukumba district in controlling operationa l cost by performing budgetary discipline in doing any activity This system will make the tourism department Bulukumba district discipline in every expenditures of each activity Similarly the achievement can be judged based on the comparison between actual and budget set utilization operational budget at the Department of tourism and Bulukumba district has managed to create the main function of the budget as a planning and control tool.